Investigating Urban Crime Pattern and Accessibility Using Geographic Information System in Bandung City - Setiawan, Iwan; Dede, Moh.; Sugandi, Dede; Agung Widiawaty, Millary (KnE Social Sciences, 2019)
Urban crime is unplanned change from urban development processes. Understanding of urban crime is necessary for crime prevention and increase urban living quality. The geographical approach in urban crime analysis can analyze crime pattern using a geographic information system, also investigate a correlation between crime and environmental condition. This research is conducted to analyze the relationships between urban crime and urban accessibility in Sumur Bandung as the region with the highest crime in Bandung City. Urban crime pattern can be determined using geographic information systems through kernel density estimation, whereas urban accessibility is obtained via network indices methods. The correlation between urban crime pattern and urban accessibility is determined from statistical tests. The results show there is a significant positive relationship between urban crime and urban accessibility in Sumur Bandung Sub-District. Urban crime pattern is concentrated in Braga and Babakan Ciamis. Crime will increase in a more accessible area, thus crime prevention effort through physical access controlling regulation in the urban region.